A novel bulk metallic glass joining mechanism based on electro pulsive technology. (May 2022) - Yang, Yang; Kong, Jian; Dong, Kewei; Liu, Xiangkui; Wang, Qipeng; Song, Xinxiang; Feng, Shuai
Abstract: We presented an electro pulsive joining method to join bulk metallic glass and systematically studied the mechanism of the joining process. Zr35 Ti30 Cu7.5 Be27.5 sheets were chosen as the representative BMG, and the experiments were performed in air with electro pulsive energy density ranging from 78.1 J/mm 2 to 295.5 J/mm 2 . The thermodynamic behaviors of the joining process with different pulse currents were analyzed by utilizing X-ray diffraction (XRD) and differential scanning calorimeter (DSC), and it suggests that the glass transition temperature ( T g ) and crystallization temperature ( T x ) shift distinctly to the high-temperature region as the heating rate increases. Hence, it reveals three different join modes during bonding: supercooled liquid phase joining, crystallization joining, and liquid phase joining. A diagram of temperature versus heating rate obtained by varying the pulse current was drawn, and it further proved that the Zr35 Ti30 Cu7.5 Be27.5 bulk metallic glass could be joined in the liquid phase, crystallization, and supercooled liquid phase. The joint's shearing tests showed that the joint's average strength boned at the three different states were 837 MPa, 1467 MPa, and 1276 MPa, respectively. Furthermore, it proved that the electro pulsive joining method could provide a universal way to join bulk metallic glass. Highlights: The study reveals three joining modes: supercooled liquid phase joining, crystallization joining, and liquid phase joining. A diagram of temperature versus heating rate obtained by varying the pulse current was developed. The T~β diagram provides useful theoretical guidance for the development of the joining processing of BMGs.